The Effect of Tou Nong San on Transplanted Tumor Growth in Nude Mice. (18th February 2015) - Fang, Liang-Hua; Wang, Rui-Ping; Hu, Shou-You; Teng, Yu-Hao; Xie, Wei-Bing
Abstract : Tou Nong San (TNS) is a traditional Chinese medicinal decoction used to treat sores and carbuncles. It contains four herbal drugs and one animal medicine: Radix Astragaliseu Seu Hedysari, Angelica sinensis, Ligustici Chuanxiong, Spina Gleditsiae, and stir-baked Squama Manis. Previous studies have shown that it has anticancer effects. This report validates in vivo antitumor properties of TNS. The compounds contained in TNSE were confirmed by liquid chromatographmass spectrometer (LC-MS) analysis. The in vivo antitumor activity of TNS extract (TNSE) was tested by feeding it to athymic mice harboring a human colonic tumor subcutaneous xenograft. Toxicity was monitored by recording behavior and weight parameters. Seven compounds were detected in TNSE by LC-MS. TNSE was fed to athymic mice for 2 weeks. No adverse reactions were reported. Compared to the control group, administration of TNSE to tumor bearing mice significantly reduced both tumor weight and volume. The expressions of p-PI3K, p-AKT, p-mTOR, p-p70s6k1, VEGF, and CD31 were significantly reduced, the expression levels of cleaved Caspase-9 and cleaved Caspase-3 were significantly increased in the TNSE groups compared to the control group as determined by western blot and immunohistochemistry. TNSE produced anticolonic cancer effects and the underlying mechanisms involved inhibition of the PI3K/AKT signal transduction pathway, inhibition of angiogenesis, and promotion of apoptotic proteins.